MANAJEMEN PROGRAM BAHASA ARAB DALAM PELAKSANAAN WAJIB BERBAHASA - Dimas Zuhri Ahmad; Abdulloh Muqofie; Khairunnisa Khairunnisa; Eman Sulaeman; Sarta Sarta; Fajar Shihab; Yuyun R. Uyuni (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Compulsory Arabic is a program to improve students' language skills. Pesantren creates an Arabic-speaking environment so that students can hone their active Arabic language skills. However, in its implementation, the average student still tends to use Indonesian in their daily lives. To continue to run an effective Arabic environment, pesantren caregivers apply management functions in implementing the program, so that students have active Arabic language skills. This study aims to describe management functions related to planning, organizing, implementing, and evaluating Arabic language programs. The research approach uses qualitative. The results of the study are as follows: 1) Planning is carried out at the beginning of the year meeting; 2) The organization consists of the Deputy Caregiver, Field Coordinator, Advisory Board and Student Organization; 3) The implementation has been carried out well; 4) Evaluation of students is carried out by oral and written tests. Nurul Ilmi Darunnajah 14 Islamic Boarding School has carried out this management function in the Arabic language program and in order to continue to make improvements for the creation of the objectives of the Arabic language program in the pesantren